Analysis of Prospective Elementary School Teachers’ Scientific Presentation Skills Through STEM Instructional - Permas Hikmatunisa, Nenden; Wulan, Neneng Sri; Fajrussalam, Hisny; Yogiarni, Tiara; Nuraeni, Fitri; Putri, Hafiziani Eka; Alindra, Afridha Laily; Ravy, Hun (Bulletin of Science Education, 2024)
Prospective elementary school teachers should not only master knowledge of content material, techniques for creating a work, and proficiency in practical skills. But also how to communicate them effectively and be able to have excellent scientific presentation skills. This is because they will become teachers who must have good scientific presentation skills. There are several aims to conduct this research such as analyzing prospective elementary school teachers’ scientific presentation skills through STEM instructional environment, determining the current levels of scientific presentation skills among prospective elementary school teachers per each indicator, and how STEM approach as an instructional environment is applied in the classroom. The method used in this research is descriptive qualitative, and the result for scientific presentation skills in total mostly prospective elementary school teachers in a high-level category. The current level is mostly high for how STEM practicums are created and how to use teaching media, the rest of the indicators (content mastery, language style, physical, verbal, vocal expression, timeliness, and confidence) in the medium-level category for scientific presentation skills. STEM can be one of the instructional environments to train the scientific presentation skills of prospective elementary schools. The summary of this research, the scientific presentation skills of prospective elementary school teachers are at a high level for the category through STEM instructional environment. Keywords: Scientific Presentation Skills, STEM Instructional Environment